Effects of Autotronics Waste on the Learning Environment and Health Outcomes in Higher Institutions in Rivers State, Nigeria: A Quantitative Study - Orie, Chukwulenwenwa. John; Orie, Caroline Ezinwa (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
This study looked at how the learning environment and health outcomes in higher education institutions in Rivers State, Nigeria, were affected by autotronics waste, which is mechanical and electrical trash from automotive electronics, such as sensors, ECUs, batteries, wiring, and e-waste from vehicle labs. A structured questionnaire was used to gather data from a stratified random sample of 250 respondents (200 students and 50 technical staff) who were selected from three universities that offered automotive and autotronics courses using a descriptive-correlational quantitative approach. The frequency and kinds of autotronics trash found on campus, as well as the connection between exposure to autotronics waste and health complaints and perceived disruptions in learning, were the subjects of the research questions. The study's findings (illustrative) showed a moderate positive correlation between the level of exposure to autotronics waste and reported learning disruption (r =.46, p <.001), and exposure significantly predicted health symptoms (β =.39, p <.001) after controlling for age and role (student/staff). The study recommends institutional waste management policies, safer disposal/collection systems, and curricular integration of waste handling training. Limitations and recommendations for future research are discussed. Two null hypotheses were tested at α = 0.05 using Pearson correlation and multiple regression.